2020
DOI: 10.1088/2515-7655/ab6f4a
|View full text |Cite|
|
Sign up to set email alerts
|

Towards highly efficient thin-film solar cells with a graded-bandgap CZTSSe layer

Abstract: A coupled optoelectronic model was implemented along with the differential evolution algorithm to assess the efficacy of grading the bandgap of the Cu 2 ZnSn(S ξ Se 1−ξ ) 4 (CZTSSe) layer for enhancing the power conversion efficiency of thin-film CZTSSe solar cells. Both linearly and sinusoidally graded bandgaps were examined, with the molybdenum backreflector in the solar cell being either planar or periodically corrugated. Whereas an optimally graded bandgap can dramatically enhance the efficiency, the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Finally, we considered the sinusoidally nonhomogeneous bandgap described by Eq (3). Values of J sc ,V oc , η, F F and % reduction in η are shown in Table 1.…”
Section: Numerical Results and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we considered the sinusoidally nonhomogeneous bandgap described by Eq (3). Values of J sc ,V oc , η, F F and % reduction in η are shown in Table 1.…”
Section: Numerical Results and Conclusionmentioning
confidence: 99%
“…Accordingly, either the red part (620-700 nm wavelength) or the bluish-green part (400-550 nm wavelength) of the incoming solar spectrum must be substantially reflected so that it becomes mostly unavailable for the photovoltaic generation of electricity. Therefore, we used an optoelectronic model of CZTSSe solar cells 3 to optimize them for maximum power conversion efficiency while reflecting either red photons or blue-green photons.…”
Section: Optoelectronic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been experimentally demonstrated that J sc can be improved without reducing V oc by grading the bandgap energy of the absorber layer in CZTSSe solar cells [7]. Detailed optoelectronic modeling indicates that the proper grading of the bandgap energy of the absorber layer can enhance both V oc and J sc in thin-film solar cells [10,11]; efficiencies as high as 27.70% and 21.74% have been predicted for CIGS solar cells [10] and CZTSSe solar cells [11], respectively.…”
mentioning
confidence: 94%
“…Thereafter, the electron-hole-pair generation rate G(z) was determined in the ZnO, CdS, CIGS, and CZTSSe layers of the double-absorber solar cell [10], assuming normal illumination by unpolarized polychromatic light endowed with the AM1.5G solar spectrum [20]. The frequencydependent relative permittivity of every material in the double-absorber solar cell is available elsewhere [10,11].…”
mentioning
confidence: 99%